Ultrasonographic Appearance of the Lower Extremity Arteries After Femoropopliteal Bypass Surgery. (May 2023) - Kalinin, Roman; Suchkov, Igor; Klimentova, Emma; Mzhavanadze, Nina; Shanaev, Ivan
Objective: The aim of this study was to assess the ultrasonographic appearance of the lower extremity arteries, after a femoropopliteal bypass surgery. Materials and Methods: Ninety patients, with atherosclerotic peripheral artery disease, underwent either autologous vein (30 subjects) or synthetic femoropopliteal bypass grafting, using an end-to-side (30 subjects) or end-to-end anastomotic technique. The outcomes were compared to 30 volunteers, who were recruited to serve as healthy controls. A lower extremity duplex ultrasonogram (DUS) was performed 1 year after treatment. The healthy volunteers underwent DUS at the point of being included in the study. Results: In healthy volunteers, the angle between the profunda femoris artery (deep femoral artery, PFA) and common femoral artery (CFA) did not exceed 30° of angulation. The diameter of the CFA, in the bifurcation area, was 9.8 ± 1.5 mm. The bypass patency rates, CFA diameter, PFA angle, and neointimal hyperplasia rates differed between the groups as presented. Conclusion: The results that were obtained may indicate the importance of bypass graft surveillance, using DUS, with precise analysis of the topography and geometry of the lower extremity arteries and vascular conduits, during the perioperative period. In addition, in this cohort, femoropopliteal bypass procedures were associated with an increase in the angle of the PFA from 30° to 80° of angulation. An increase in the diameter of the CFA in the area of the proximal anastomosis from 9.8 to 15.1 mm was also noted. In these patients, the saphenous vein bypasses were associated with minimal changes of the vascular geometry and better patency rates.